Oscillation of the rectangular thin plate when making mention of the creep of material - Da, Hoang Van (Vietnam Journal of Mechanics, 1983)
In this work, the author have modeled and set up the equation of motion of the rectangular thin plate with regard to the creep of material in critical case. The asymptotic solution was constructed by means of method [3] for autonomous system. To illustrate the presented method a concrete example had been analyzed. It is seen that the physical character of the material decreases the amplitude of the oscillation as viscous friction.